Yes, we should abandon pre-treatment positional testing of the cervical spine. (October 2020) - Hutting, Nathan; Kranenburg, Hendrikus Antonius "Rik"; Kerry, Roger
Abstract: Although there seems to be no causality between cervical spine (CS) manipulation and major adverse events (MAE), it remains important that manual therapists try to prevent every potential MAE. Although the validity of positional testing for vertebrobasilar insufficiency (VBI) has been questioned, recently, the use of these tests was recommended. However, based on the low sensitivity of the VBI tests, which may result in too many false-negative results, the VBI tests seem to be less valuable in pre-manipulative screening. Moreover, because the VBI tests are unable to consistently produce a decreased blood flow in the contralateral vertebral artery in (healthy people), the underlying mechanism of the test may not be a valid construct. There are numerous cases reporting MAE after a negative VBI test, indicating that the VBI tests do not have a role in assessing the risk of serious neurovascular pathology, such as cervical arterial dissection, the most frequently described MAE after CS manipulation. Symptoms of VBI can be identified in the patient interview and should be considered as red flags or warning signs and require further medical investigation. VBI tests are not able to predict MAE and seem not to have any added value to the patient interview with regard to detecting VBI or another vascular pathology. Furthermore, a negative VBI test can be wrongly interpreted as 'safe to manipulate'. Therefore, the use of VBI tests cannot be recommended and should be abandoned. Highlights: Positional testing for vertebrobasilar insufficiency (VBI) is often used by manual therapists. The VBI tests do not seem to be important in the pre-manipulative screening. The rationale and value of the VBI tests should be questioned. A negative VBI test can easily be wrongly interpreted as 'safe to manipulate'. The use of the VBI tests cannot be recommended and should be abandoned.